2012
DOI: 10.1111/j.1751-7176.2012.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hypertension Prevalence, Awareness, Treatment, and Control Rates in Shandong Province of China

Abstract: J Clin Hypertens (Greenwich). 2012; 14:637–643. © 2012 Wiley Periodicals, Inc. The authors retrospectively examined data from 3 surveys on hypertension according to the 2010 Chinese Guidelines for the Management of Hypertension. These surveys were conducted in 1991, 1999, and 2007, and included 85,371 individuals 18 years and older who were living in Shandong Province, China. Age‐standardized prevalent hypertension increased from 15.6% in 1991 to 17.3% in 1999 and 32.7% in 2007 (both P<.0001). The ascending pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…The rates of HBP awareness, treatment and control among HBP patients in our investigation were 70.0%, 62.1% and 29.6%, respectively. These rates were higher than the HBP awareness, treatment and control rates of 30.2%, 24.7% and 6.1%, respectively, found in the 2002 China national survey2 and those found in other studies in China345678920 and in other developing countries2122, but they were lower than the respective rates of 80.6%, 71.6% and 48.4% in the 2007 to 2008 US National Health and Nutrition Examination Survey13. However, there was no similarity in age, sampling and representativeness between the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…The rates of HBP awareness, treatment and control among HBP patients in our investigation were 70.0%, 62.1% and 29.6%, respectively. These rates were higher than the HBP awareness, treatment and control rates of 30.2%, 24.7% and 6.1%, respectively, found in the 2002 China national survey2 and those found in other studies in China345678920 and in other developing countries2122, but they were lower than the respective rates of 80.6%, 71.6% and 48.4% in the 2007 to 2008 US National Health and Nutrition Examination Survey13. However, there was no similarity in age, sampling and representativeness between the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study found that 1 in 4 adults in Shandong Province had hypertension in 2011 — an estimated 16 million people. Other surveys, using different methods of sampling and analysis, found that hypertension is becoming common in Shandong Province (17,18). The prevalence of hypertension in Shandong in our study was lower than the pooled prevalence in the northern region (25.8%) and higher than that in the southern region of China (20.4%) (19).…”
Section: Discussionmentioning
confidence: 99%
“…The different characteristics of the two populations enrolled and the different methodologies applied for measuring BP levels may at least, in part, explain the observed discrepancies between the results of these two studies [16]. Another survey, performed in Brazil and including 2060 people aged between 23 and 25 years, reported a prevalence of 13.5 % of individuals having borderline BP values and 9.5 % of individuals having essential hypertension, respectively [17].…”
Section: Epidemiologymentioning
confidence: 95%